Implementation and Validation of the CIPPO Model: A Case Study at Nurul Fajri Senior High School Palasah, Majalengka Supporting SDG 4 - Fikri Hari Rustiyawan; Mohammad Afifulloh; Dian Mohammad Hakim; Ika Ratih Sulistiani Sulistiani; Muhammad Fahmi Hidayatullah; Moh. Muslim (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: To analyze the implementation and validation of the CIPPO (Context, Input, Process, Product, and Outcome) evaluation model as an educational evaluation framework to improve learning quality at Nurul Fajri Senior High School Palasah Majalengka. The study highlights the importance of comprehensive evaluation models in supporting sustainable educational improvement and achieving the objectives of Quality Education (SDG 4). Method: A qualitative program evaluation approach. Data were collected through classroom observations, semi-structured interviews with teachers, students, and school administrators, as well as document analysis. Data validation was conducted through triangulation to obtain comprehensive information regarding the implementation process of the CIPPO model. Results: The findings indicate that the implementation of the CIPPO model positively contributed to improving student engagement, teaching effectiveness, learning outcomes, and teacher satisfaction. The context component showed strong support from school management and community involvement, while the input and process components emphasized the importance of teacher development and curriculum adaptation. The outcome component demonstrated improvements in students’ academic achievement, motivation, and character development. Novelty: To provide empirical evidence regarding the application of the CIPPO model in an Islamic-based secondary school context by integrating academic achievement and character education. The findings contribute to educational evaluation practices that support sustainable quality improvement aligned with SDG 4.